2016
DOI: 10.1080/21520704.2016.1138266
|View full text |Cite
|
Sign up to set email alerts
|

The making of expert performers at Cirque du Soleil and the National Circus School: A performance enhancement outlook

Abstract: 32In this paper, an applied analysis of the psychological processes and skills necessary for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Informed by empirical work and applied intervention done within the circus context (e.g., Ménard and Hallé, 2014 ; Burtt and Lavers, 2017 ), CfD presents a continuum of competencies to be developed through and for circus artists’ optimal growth from novice to expert. Namely, it integrates four key attributes that have been shown to contribute to artists’ performance and wellbeing, including physical attributes ( Decker et al, 2019 ; Kriellaars et al, 2019 ; Barker et al, 2020 ), psychological attributes ( Shrier and Hallé, 2011 ; Filho et al, 2016 ; Ross and Shapiro, 2017 ; Donohue et al, 2018 ; van Rens and Filho, 2019 ), interpersonal and social attributes ( Filho et al, 2017 ; Filho and Rettig, 2018 ), and creative attributes ( Leroux and Batson, 2016 ). These four attributes will inform the learning domains of the intervention delivered to students to ensure that their holistic development and wellness are addressed.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Informed by empirical work and applied intervention done within the circus context (e.g., Ménard and Hallé, 2014 ; Burtt and Lavers, 2017 ), CfD presents a continuum of competencies to be developed through and for circus artists’ optimal growth from novice to expert. Namely, it integrates four key attributes that have been shown to contribute to artists’ performance and wellbeing, including physical attributes ( Decker et al, 2019 ; Kriellaars et al, 2019 ; Barker et al, 2020 ), psychological attributes ( Shrier and Hallé, 2011 ; Filho et al, 2016 ; Ross and Shapiro, 2017 ; Donohue et al, 2018 ; van Rens and Filho, 2019 ), interpersonal and social attributes ( Filho et al, 2017 ; Filho and Rettig, 2018 ), and creative attributes ( Leroux and Batson, 2016 ). These four attributes will inform the learning domains of the intervention delivered to students to ensure that their holistic development and wellness are addressed.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Since circus arts exemplifies a truly embodied cognition context, a holistic approach is required to simultaneously address cognitive, affective and performance demands ( Rokotnitz, 2018 ). There is currently no research examining holistic health interventions in circus students and limited evidence in performance artists in general; however, leaders in the field argue that integrating interventions supporting coping, resilience, and creativity as part of the circus school curriculum is key to optimize artists’ wellbeing ( Ménard and Hallé, 2014 ; Filho et al, 2016 ; Burtt and Lavers, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…21 Hence, providing an emotionally safe environment is paramount in supporting the creative growth and performance of the performers. 22 In this regard, researchers have found that emotional regulation is integral to performing artist success and that it can reduce the occurrence of accidents and near misses in contemporary circus arts. 22,23 It is thus essential for practitioners to address the emotional experiences of a significant event to help artists recognize, understand, label, express, and regulate emotional content attached to the experience.…”
Section: Psychological Considerationsmentioning
confidence: 99%
“…22 In this regard, researchers have found that emotional regulation is integral to performing artist success and that it can reduce the occurrence of accidents and near misses in contemporary circus arts. 22,23 It is thus essential for practitioners to address the emotional experiences of a significant event to help artists recognize, understand, label, express, and regulate emotional content attached to the experience. Active listening where the practitioner expresses curiosity by asking questions rather than making judgements can be a powerful tool.…”
Section: Psychological Considerationsmentioning
confidence: 99%
“…The school is geared towards high-performing circus artists in their later stages of development (see Bloom, 1985). Performers come to the school from around the world and the school is renowned for developing world-class circus artists who desire jobs in premier circus companies, such as Cirque du Soleil (Filho, Aubertin, & Petiot, 2016). This sampling strategy is consistent with the importance of targeting "informationrich cases" in qualitative inquiry (see Patton, 2002).…”
Section: Participantsmentioning
confidence: 99%